The characteristics of the Computer Supported Collaborative Learning (CSCL) through Moodle: a view on students’ knowledge construction process - Hashim, Suhaizal; Ismail, Mohd Erfy; Ismail, Affero; Masek, Alias; Ismail, Irwan Mahazir; Razali, Nizamuddin; Samsudin, Mohd Ali (Science Publishing Corporation, 2019)
Computer Supported Collaborative Learning (CSCL) is based on the pedagogical process of observation where students will learn progressively through active group interaction. CSCL is an emerging branch of the learning sciences concerned with studying on how people can learn together with the help of computers. Thus, this research was conducted to measure the characteristics of the CSCL learning environment through Moodle that assists the process of students’ knowledge construction during the teaching and learning process. The CSCL learning environment is an educational learning system which develops to help the teachers and students in managing School Based Assessment (SBA) in selected secondary school in Malaysia. Samples involved two groups of students and two Technical and Vocational Education and Training (TVET) teachers from two different schools. A total of 61 students, who were taught using CSCL approach through Moodle, underwent the process of teaching and learning using their school computer laboratory. The finding shows that the characteristics of the CSCL learning approach that used in this learning environment for the first group are at a high level with overall mean of 4.17 and the second group at moderate level with overall mean of 3.62. The result proves that the characteristics of the CSCL learning environment help students to build their knowledge during teaching and learning process at the high level with an overall mean score of 3.87. The mean of these two groups may vary according to students’ background, as well as learning environment facilities. Although, CSCL leads to students’ self-development, improving learning quality, sharing knowledge and assisting students’ in the process of building their knowledge, implementation of CSCL must first considering the technology relevant facilities, especially computer laboratory and internet accessibility in school. The implication is that designing a good CSCL must also taking into account the targeted users’ cultural background and socioeconomic factors